2019
DOI: 10.3390/coatings9080503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan-Ascorbic Acid Coatings on the Refrigerated Storage Stability of Fresh-Cut Apples

Abstract: Using natural antimicrobial substances in edible films becomes crucial to extend the shelf-life of fresh-cut fruits due to the consumers' preferences. In this study chitosan and ascorbic acid based film was used to improve the shelf-life of fresh-cut apples. Fresh-cut apple cubes were dipped in water (control), ascorbic acid (1%) or mixtures of chitosan-ascorbic acid in different ratios (1%:1%, 2%:2% or 1%:5%) for 5 min. After draining, fresh-cut apples were packed in sterile polypropylene jars and stored at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Similarly, Adiletta et al [ 75 ] revealed that fig fruit treated with CS-based coating combined with ascorbic acid (1% w / v ) exhibited higher TP content stored at 4 °C for nine days. Likewise, Özdemir and Gökmen [ 92 ] reported that application of CS and ascorbic acid based coating showed higher content and slower decline of TP content compared with the control by the end of storage in fresh-cut apples.…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Adiletta et al [ 75 ] revealed that fig fruit treated with CS-based coating combined with ascorbic acid (1% w / v ) exhibited higher TP content stored at 4 °C for nine days. Likewise, Özdemir and Gökmen [ 92 ] reported that application of CS and ascorbic acid based coating showed higher content and slower decline of TP content compared with the control by the end of storage in fresh-cut apples.…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 99%
“…In CS-coated litchi, sweet cherry, blueberry, strawberry, longan, and pomegranate fruits have been detected a lower reduction of anthocyanin content compared to uncoated ones probably due to their enzymatic degradation owing to anthocyanase, PPO, and peroxidase (POD) throughout the storage period [ 11 , 45 , 49 , 64 , 66 , 67 , 70 , 78 , 83 , 92 , 97 , 104 , 114 ].…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 99%
“…Sogvar et al [11] reported that the application of Aloe vera in combination with AA on strawberry fruit improves the postharvest life by maintaining fruit quality attributes as well as firmness, solid soluble content, titratable acidity, vitamin C, anthocyanin, total phenolic, and total antioxidant activity and reduces decay by suppression of total aerobic mesophilic bacteria, yeasts, and mold growth. Other studies showed that coating with chitosan and ascorbic acid is an effective solution for inhibiting the growth of microorganisms, retarding enzymatic browning reactions, and reducing the weight loss of fresh-cut apples during refrigerated storage [22].…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Chitosan and AA also exhibited synergistic effects, such as wound healing capability on skin 35 and storage stability of fruits. 36,37 The chitosan colloid prepared in AA solution was found to be stable in over a wide pH range from acidic to alkali conditions and exhibits a high thermal stability. This method may offer versatile ways of chitosan nanoparticle to be used as a carrier for foods, cosmetics, drugs, and so on.…”
Section: Introductionmentioning
confidence: 99%